Managing Perbadanan Tabung Pendidikan Tinggi Nasional (PTPTN) loans among diploma students in UiTM Sarawak / Nurshaima Napis, Nur Fahidah Ali and Norfazila Jenal - Napis, Nurshaima; Ali, Nur Fahidah; Jenal, Norfazila (2010)
The act providing money in the form of a loan or capital is known as finance and something that everyone from governments to the private individual uses. It is also a branch of economics that studies the management of money and other assets. As information, management can be defined as the act or art of managing; the manner of treating, directing, carrying on, or using, for a purpose; conduct; administration; guidance; control; as, the management of a family or of a farm; the management of state affairs. Financial management entails planning for the future of a person or a business enterprise to ensure a positive cash flow. It includes the administration and maintenance of financial assets. Besides, financial management covers the process of identifying and managing risks. The primary concern of financial management is the assessment rather than the techniques of financial quantification. A financial manager looks at the available data to judge the performance of enterprises. Managerial finance is an interdisciplinary approach that borrows from both managerial accounting and corporate finance. Some experts refer to financial management as the science of money management. The primary usage of this term is in the world of financing business activities. However, financial management is important at all levels of human existence because every entity needs to look after its finances.